A retrospective review of post-intubation sedation and analgesia practices in a South African private ambulance service - de Kock, Joalda Marthiné (Division of General Surgery, 2022)
Introduction: Adequate post-intubation sedation and analgesia (PISA) practices are important in the pre-hospital setting where vibration and noise of the transport vehicle may contribute to anxiety and pain in the patient. Inadequate post-intubation practices may lead to long-term detrimental effects in patients. Despite this, these practices are poorly described in the prehospital setting. This study aims to describe the current pre-hospital PISA practices in a private South African emergency medical service. Methodology: Patient report forms (PRF) of intubated patients between 1 Jan 2017 and 31 Dec 2017 from a single private ambulance service were reviewed. Data was analysed descriptively. Correlations were calculated with Spearman's Rank correlations and group differences were calculated with Independent T tests and Mann-Whitney U tests. Significant correlations were entered into a binomial regression model to determine predictive value of receiving PISA. Results: The number of PRFs included for analysis was 437. Of these, 69% of patients received some type of PISA. The estimated time from intubation to 1st PISA ranged from 9 to 12 minutes. There were statistically significantly more PISA interventions in patients who had received Rocuronium (p< 0.01). There was weak but significant correlation between the number of interventions and the mean arterial pressure, (rs = 0.17, p< 0.01) and Glasgow Coma Scale (rs = -0.15, p< 0.01) prior to intubation, along with the transport time to hospital (rs = 0.23, p< 0.01). Conclusion: The PISA practices in the South African pre-hospital setting is comparable to international pre-hospital settings. The time to 1st PISA appears to be shorter in the SA setting. There is an increased number of interventions in the patients who received Rocuronium, which may indicate practitioners being mindful of wakeful paralysis. Practitioners also take the level of consciousness and blood pressure prior to intubation into account when administering PISA. Longer transport times attribute to patients receiving more PISA interventions.